2004
DOI: 10.1097/01.icl.0000133241.56713.2f
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Intrastromal Gatifloxacin Crystal Deposits After Penetrating Keratoplasty

Abstract: Gatifloxacin, a fourth-generation fluoroquinolone, can cause intrastromal macroscopic crystalline deposits through a compromised corneal epithelium, similar to what has been described for ciprofloxacin, a second-generation fluoroquinolone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Fluoroquinolones such as gatifloxacin and ciprofloxacin are not recommended for intrastromal injection as this can result in macroscopic crystalline deposits. 11 In our experience, an intrastromal antibiotic agent was an effective alternative to the excision of infected tissue and tectonic grafting. The deep stromal location of the keratitis made identification of the infective organism difficult.…”
Section: Discussionmentioning
confidence: 96%
“…Fluoroquinolones such as gatifloxacin and ciprofloxacin are not recommended for intrastromal injection as this can result in macroscopic crystalline deposits. 11 In our experience, an intrastromal antibiotic agent was an effective alternative to the excision of infected tissue and tectonic grafting. The deep stromal location of the keratitis made identification of the infective organism difficult.…”
Section: Discussionmentioning
confidence: 96%
“…[13][14][15][16][17][18] SchlotzerSchrehardt et al 19 reported corneal stromal calcium deposition in all levels of the stroma, secondary to topical dexamethasone phosphate therapy in the context of chronic keratoconjunctivitis in a patient with StevensJohnson syndrome. In the latter study, histopathological analysis of the corneal button evidenced calcium deposits closely associated with intracellular and pericellular accumulations of glycosaminoglycans, suggesting a possible role of dexamethasone phosphate treatment altering the glycosaminoglycan metabolism of stromal keratocytes in the calcification process.…”
Section: Discussionmentioning
confidence: 99%
“…4 In contrast to older fluoroquinolones, there is currently only one report of gatifloxacin crystalline deposition occurring in a deepithelialized corneal graft after penetrating keratoplasty. 5 The authors later reported that the crystalline deposits were improved, but still present in the graft, after 2 years. 6 This case is the first report of gatifloxacin crystalline deposition in the setting of an intact corneal epithelium.…”
mentioning
confidence: 97%